Enhanced fluoride removal from water by nanosized cerium oxides impregnated porous polystyrene anion exchanger. (January 2022) - Dong, Hao; Tang, Huan; Shi, Xinxing; Yang, Wenlan; Chen, Wenjing; Li, Han; Zhao, Yu; Zhang, Zhengyong; Hua, Ming
Abstract: Efficient elimination of fluoride from wastewater is an urgent need for ensuring water safety. In the present study, a stable and reusable nanocomposite (NCO@PAE) was synthesized by impregnating nanosized cerium oxides (NCO) inside a porous polystyrene anion exchanger (PAE) host for efficient fluoride removal from wastewater. The newly fabricated NCO@PAE exhibited excellent resistance to acid and alkali environment, allowing it to be utilized in a wide pH range (2–12). Fluoride uptake onto NCO@PAE was a pH-dependent process, which could reach the maximum capacity at pH 3.0. Compared with its host PAE, NCO@PAE showed conspicuous adsorption affinity towards fluoride in the coexistence of other competing anions at high concentrations. Adsorption kinetics confirmed its high efficiency for achieving equilibrium within 120 min. Fixed-bed adsorption runs demonstrated that the effective processing capacity of NCO@PAE for synthetic fluoride-containing wastewater (initial fluoride 2.5 mg/L) was about ~330 BV (bed volume), while only 22 BV for the host PAE. The exhausted NCO@PAE could be effectively revived by a simple in-situ desorption method for long-term cycle operation without conspicuous capacity loss. All the results indicated that NCO@PAE is a reliable and promising adsorbent for water defluoridation. Graphical abstract: Image 1 Highlights: A stable and reusable nanocomposite NCO@PAE was fabricated for fluoride removal. Nanosized Ce oxide was embedded in a porous polystyrene host to acquire selectivity. NCO@PAE could selectively capture fluoride in the coexistence of competing anions. As-laden NCO@PAE could be effectively revived for cyclic utilization.